General Education Teachers’ Knowledge of and Attitudes Toward Students with Attention Deficit/Hyperactivity Disorders: Are They Still Being Overlooked and Underserved? - Wallace Taylor, Roben; Ringlaben, Ravic P. (Journal of the American Academy of Special Education Professionals, 2013)
This study was an investigation of general education teachers’ knowledge and attitudes regarding students with Attention Deficit/Hyperactivity Disorder (AD/HD). Of interest were (a) the extent of teachers’ knowledge about characteristics of AD/HD; (b) the extent of teachers’ knowledge of teacher skills appropriate for educating students with AD/HD; and (c) the extent of teachers’ willingness to accommodate students with AD/HD. There was an initial assessment of teachers’ knowledge and attitudes (pretest) followed by a workshop designed to increase teachers’ knowledge and improve their attitudes. An additional assessment of their knowledge and attitudes (posttest) was then administered. Results and implications for future research are discussed within this article.